Conference management system / Athirah Mohamedsha - Mohamedsha, Athirah (2013)
This paper introduces the conference management system, a web based conference management system that focuses on conference management. I developed a content management system for conference management to manage the conference process and provide conference service. The development of the system is to help people who want to create or join the conference. The system will also be used by UiTM(Terengganu) for any conference event thus creating a standardization for all conference management in UiTM(Terengganu).The system are developed through using extreme programming methodology, the methodology consists of 4 phases which consist of Exploration phase, Planning phase, Iterations to release phase and productionizing phase. Exploration phase consist of analysing the current management system that is being used in UiTM (Terengganu), Planning phase will include the time estimation to complete the project. Iterations to release plan will consist the development of the project and lastly the productionizing phase where verification and validation is being done. It is found that the system is able to be use, with none of the respondents either disagrees of strongly agree with any of the system‟s characteristics. The system should be expanded more by having more features that help increase the usability of the system.